Effects of Oregano Aromatic Water (Oreganum onites L.) Supplementation on Diets of Lactating Dairy cows on Milk Production Performance, Metabolic Health and Antioxidative Defense Mechanism - Özkaya, S; Taşkın, K; Erbaş, S; Ozkan, O; Neja, W; Tüzün, CG; Şanlı, ER (Journal of the Hellenic Veterinary Medical Society, 2024)
This study aimed to validate the effect of oregano aromatic water (OAW) on blood parameters, oxidative stress, and production and composition of milk when used as a feed additive. Thirty lactating Holstein cows (average 570 kg), average 74 days in milk and 2.44 lactation number, were randomly divided into three groups for a period of 60-days. These groups included: (G1) control ration, (G2) control ration + OAW (10 mg/kg of DM), (G3) control ration + OAW (20 mg/kg of DM). Milk production (MP) were unaffected by OAW doses (P>0.05). The supplementation of OAW did not affect the milk composition, and somatic cell count (SCC) (P>0.05). OAW supplementation did not affect blood biochemical values except ketone and glucose. The glucose value increased as the ketone decreased with OAW supplementation (P<0.05). The hematological blood values were not found to be significant. OAW significantly decreased Total oxidant capacity (TOC) and oxidative stress index (OSI) while increasing Total antioxidant capacity (TAC). The current study’s findings indicated that OAW can be used as a feed additive to improve cow health and milk production.